INTRACHOLECCYSTIC PAPILLARY NEOPLASM AS AN INCIDENTAL FINDING IN CHOLECYSTECTOMY (International Seven Journal of Health Research, 2024)
Report of a case of a young adult patient who underwent cholecystectomy with an incidental finding of papillary gallbladder neoplasia. This is a study whose information was collected from the medical records of a single 39-year-old male patient who underwent routine consultation and complementary tests for underlying disease, with an incidental finding of vesicular polyps on imaging, presenting significant size and, when identifying smoking as a risk factor and possible segment loss,  videolaparoscopic cholecystectomy was chosen. The anatomopathological study identified a papillary neoplasm of the gallbladder, potentially malignant, but with no histological transformations. Cholecystectomy is the main approach to stones and vesicular polyps to avoid more serious complications. The nonspecific clinical practice does not allow the identification of the exact cause, when related to malignant neoplasia, until the anatomopathological study brings to light the development of the tumor and neoplastic histological transformations, in addition, such pathologies as gallbladder cancers are rare, but they are more common in women, in the presence of overweight and in smokers, having the same risk factors as simple calculous cholecystitis.